ON THE DEFLATIORY NATURE OF BITCOIN - Srdjan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Unique assemblage of technical solutions and economic concepts called Bitcoin was presented at the end of 2008. For a long time, this paying system was not in the focus of economic or legal research, but nowadays it is almost impossible to conduct and complete research on monetary obligations without short review at least on how this system operates. Being so, it may come as a surprise that, even with all the research conducted recently, we still do not have definite answers to some of the most fundamental questions. One of them is whether Bitcoin is form of money or something entirely different. We believe that Bitcoin was designed primarily, not with the intention to create money in a strict sense, but with the intention to provide platform for transfer of value form one party to another in as little time as possible, with no intermediaries, at low(er) price, all that without compromising safety of the participants or assets. In other words, the idea was to make transfer of value as effective as possible. Yet, Bitcoin has a capacity to take on the role of the money in a most strict sense. That capacity was even recognized in court cases and comes to the fore mainly in times of crisis. And with respect to that capacity, in this paper we present results of the primarily empirical, but also theoretical research conducted previously on bitcoins volatile, but still very deflationary nature and its effect on monetary obligations. Concretely, we believe that, with the analogy to foreign currency clauses, cryptocurrencies, primarily bitcoin, can also be used as hedging instrument to prevent negative effects of domestic currency depreciation. The idea might be controversial for number of reasons. Certainly, one of them is related to very volatile nature of bitcoin “price”. Yet, in that context, we stressed that periodic depreciation of its value does not mean that bitcoin is inflationary. On the contrary, bitcoin is deflationary by nature. Different built in mechanisms, but also new ways of application emphasize that nature. So, in this paper we use different techniques of analytical method, first to single out various deflatory mechanisms, both preprogramed and factual ones, and after that to describe them. We also use synthetical method and its techniques, primarily abstraction and generalization, to sum up data which confirms our main hypothesis that the bitcoin is by nature deflatory despite its volatility, therefore it can be used as hedging mechanism in form of cryptocurrency clauses.